First-line afatinib for advanced EGFRm+ NSCLC: Analysis of long-term responders in the LUX-Lung 3, 6, and 7 trials. (July 2019) - Schuler, Martin; Paz-Ares, Luis; Sequist, Lecia V.; Hirsh, Vera; Lee, Ki Hyeong; Wu, Yi-Long; Lu, Shun; Zhou, Caicun; Feng, Jifeng; Ellis, Stuart H.; Samuelsen, Carl H.; Tang, Wenbo; et al.
Highlights: In LUX-Lung 3/6/7, 10–12% of afatinib-treated patients were long-term responders. LTRs included common and uncommon EGFR mutations and patients with brain metastases. Among LTRs, median PFS was 49.5, 55.5, and 42.2 months in LUX-Lung 3/6/7. Frequency of afatinib dose reduction was consistent with overall study populations. PROs were stable, with slight improvements after 3 years of afatinib treatment. Abstract: Objectives: In patients with advanced epidermal growth factor receptor mutation-positive ( EGFR m+) non-small cell lung cancer (NSCLC), first-line afatinib significantly improved progression-free survival (PFS) and objective response vs. platinum-doublet chemotherapy in the phase III LUX-Lung 3 and LUX-Lung 6 trials, and significantly improved PFS, time to treatment failure and objective response vs. gefitinib in the phase IIb LUX-Lung 7 trial. We report post-hoc analyses of efficacy, safety and patient-reported outcomes (PROs) in afatinib long-term responders (LTRs) in these trials. Methods: Treatment-naïve patients with stage IIIB/IV EGFR m + NSCLC randomized to afatinib in LUX-Lung 3/LUX-Lung 6/LUX-Lung 7 were included in the analysis. Patients treated with afatinib for ≥ 3 years were defined as LTRs. Results: In LUX-Lung 3, LUX-Lung 6, and LUX-Lung 7, 24/229 (10%), 23/239 (10%) and 19/160 (12%) afatinib-treated patients were LTRs. Baseline characteristics were similar to the study populations, except for the proportions of women (LUX-Lung 3/LUX-Lung 6 only; 92/78% vs. 64% overall) and Del19-positive patients (63–79% vs. 49–58% overall). Median treatment duration among LTRs was 50, 56 and 42 months, and median PFS was 49.5, 55.5, and 42.2 months in LUX-Lung 3/LUX-Lung 6/LUX-Lung 7, respectively. Median overall survival could not be estimated. Frequency of afatinib dose reduction was consistent with the LUX-Lung 3/LUX-Lung 6/LUX-Lung 7 overall populations. PROs were stable in LTRs, with slight improvements after 3 years of afatinib treatment vs. baseline scores. Conclusions: In the LUX-Lung 3/LUX-Lung 6/LUX-Lung 7 trials, 10–12% of afatinib-treated patients were LTRs. Long-term afatinib treatment was independent of tolerability-guided dose adjustment and had no detrimental impact on safety or PROs.